Soft Polydimethylsiloxane Thin Elastomeric Films by In Situ Polymerization to be Used as Dielectricum in Actuators. Issue 9 (6th April 2014) - Circu, Monica V.; Ko, Yee Song; Gerecke, Andreas C.; Opris, Dorina M.
<x xml:space="preserve">Abstract</x> A low‐viscosity, solvent‐free process for the fabrication of thin silicone films for dielectric elastomer actuators is presented. Octamethylcyclotetrasiloxane and specially designed co‐monomers that function as cross‐linkers are pre‐polymerized to a liquid of low viscosity. This liquid is used to prepare thin films, which are then fully polymerized to a highly transparent, cross‐linked elastomer. The mechanical and electromechanical properties of the films are easily tuned by altering the amount of cross‐linker co‐monomer used.<inline-graphic xlink:href="ark:/27927/pgh177nfn9s" content-type="mame201300457-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />